Current status of the TwinMic beamline at Elettra: a soft X‐ray transmission and emission microscopy station. (12th October 2016) - Gianoncelli, Alessandra; Kourousias, George; Merolle, Lucia; Altissimo, Matteo; Bianco, Anna
Abstract : A detailed description of the TwinMic beamline installed at Elettra, Italy, is presented. The beamline hosts a unique soft X‐ray microscope supporting both transmission and scanning X‐ray microscopy (TXM and STXM, respectively) within the one instrument. The beamline presently fosters the following techniques: STXM, TXM and ptychography, that can be combined with low‐energy X‐ray fluorescence and X‐ray absorption near‐edge structure spectroscopies. A detailed update of the design, operational modes and future upgrades of the TwinMic beamline is presented. Abstract : The current status of the TwinMic beamline at Elettra synchrotron light source, that hosts the European twin X‐ray microscopy station, is reported. The X‐ray source, provided by a short hybrid undulator with source size and divergence intermediate between bending magnets and conventional undulators, is energy‐tailored using a collimated plane‐grating monochromator. The TwinMic spectromicroscopy experimental station combines scanning and full‐field imaging in a single instrument, with contrast modes such as absorption, differential phase, interference and darkfield. The implementation of coherent diffractive imaging modalities and ptychography is ongoing. Typically, scanning transmission X‐ray microscopy images are simultaneously collected in transmission and differential phase contrast and can be complemented by chemical and elemental analysis using across‐absorption‐edge imaging, X‐ray absorption near‐edge structure or low‐energy X‐ray fluorescence. The lateral resolutions depend on the particular imaging and contrast mode chosen. The TwinMic range of applications covers diverse research fields such as biology, biochemistry, medicine, pharmacology, environment, geochemistry, food, agriculture and materials science. They will be illustrated in the paper with representative results.